The Global Welfare Impact of China : Trade Integration and Technological Change - Di Giovanni, Julian (IMF Working Papers; Working Paper ;, 2012)
This paper evaluates the global welfare impact of China's trade integration and technological change in a quantitative Ricardian-Heckscher-Ohlin model implemented on 75 countries. We simulate two alternative productivity growth scenarios: a "balanced" one in which China's productivity grows at the same rate in each sector, and an "unbalanced" one in which China's comparative disadvantage sectors catch up disproportionately faster to the world productivity frontier. Contrary to a well-known conjecture (Samuelson, 2004), the large majority of countries in the sample, including the developed ones, experience an order of magnitude larger welfare gains when China's productivity growth is biased towards its comparative disadvantage sectors. We demonstrate both analytically and quantitatively that this finding is driven by the inherently multilateral nature of world trade. As a separate but related exercise we quantify the worldwide welfare gains from China's trade integration.